Multicultural School Management in the Development of Religious Inclusiveness Culture in SMK Bhakti Karya Parigi West Java (Program Studi Pendidikan Agama Islam, 2022)
Education as a sub-culture of society should be able to contribute to building harmony above differences, especially religious differences. One of the efforts that can be taken in this regard is the practice of multicultural school management. The existence of multicultural school management shows that schools officially recognize diversity through policies to organize and accept this diversity. Through the implementation of multicultural school management at SMK Bhakti Karya Parigi Pangandaran, West Java, it is hoped that education will be able to contribute to developing religious inclusiveness in social life. The method used in this research was field research using a qualitative approach. The main subjects in this study were the principal and manager of SMK Bhakti Karya Parigi Pangandaran, West Java. In this study, the material object was SMK Bakti Karya Parigi, and the formal object was multicultural school management in developing inclusive religious culture. Data collection techniques used participatory observation, interviews, documentation, and data triangulation. Meanwhile, the data analysis employed the Spradley model data analysis technique with domain, taxonomy, componential, cultural, and triangulation analysis. The results revealed that the implementation of multicultural school management at SMK Bakti Karya has included all management functions, from planning, organizing, implementing, and supervising schools and one of the results of the multicultural school management practice is the development of religious inclusiveness culture in the school environment and the community. It can be proven by the school's ability to accommodate differences, especially religious differences, in the school environment to reach school goals together.